Ekspresi AgNOR dan Ekspresi Ki-67 pada Grading Adenokarsinoma Prostat - Roza Rita; Delyuzar; Lidya Imelda Laksmi (Majalah Patologi Indonesia, 2020)
BackgroundProstate cancer is the second most common cancer and fifth most common cancer cause of death in males. Tissue biopsy is a goldstandard examination to diagnose prostate cancer. One of the hallmarks of cancer is increased activity of cell proliferation. Thisactivity can be detected with Ki-67 and AgNOR (Argyrophilic nucleolar organizing region). The aim of this study is to analyzedcorrelation between AgNOR and Ki-67 expression in grading of prostated adenocarcinoma.MethodsThis analytic cross-sectional study was held in Laboratory of Anatomical Pathology of Medical Faculty of USU/ RSUP H. AdamMalik Medan. Thirty paraffin blocks diagnosed with prostate adenocarcinoma were stained with H&E and p63 immunohistochemistrythen evaluated based on Gleason’s histopathological grading and stained with Agnor and Ki 67.ResultsAgNOR expression yang diperoleh pada grading adenokarsinoma prostat group 1, 2, 3, 4, dan 5 berturut-turut adalah 43; 32,40(±14,54); 64,29 (±28,2); 59,5 (±28,32); 69,22 (±29,26). Ekspresi Ki-67 pada setiap grading adenokarsinoma prostat group 1, 2, 3, 4,dan 5 secara berurutan adalah 43; 32,4 (±14,53); 64,29 (±28,2), 59,5 (±28,31); 69,22 (±29,26). Statistical analyses showed thatthere was no significantly correlation between grading of prostate adenocarcinoma and AgNOR expression (p=0.065), and Ki-67expression (p=0.18). Nevertheless, a significantly correlation between KI-67 expression and grading of prostate adenocarcinomawas found (p=0.34).ConclusionKi-67 could be used as prognostic indicator for prostate adenocarcinoma.